2016
DOI: 10.1109/lawp.2015.2434823
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing of Multilayer Millimeter-Wave Yagi-Uda Antennas on Flexible Substrates

Abstract: This work presents two high-gain, multi-director Yagi-Uda antennas for use within the 24.5 GHz ISM band, realized through a multilayer, purely additive inkjet printing fabrication process on a flexible substrate. Multilayer material deposition is used to realize these 3D antenna structures, including a fully-printed 120 µm thick dielectric substrate for microstrip to slotline feeding conversion. The antennas are fabricated, measured, and compared to simulated results showing good agreement and highlighting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…These authors also showed a 14.6 dB return loss at 25.8 GHz. The first demonstration of a Yagi-Uda antenna was done a year earlier using IJP Ag (1.1 × 10 7 S/m) and SU-8 dielectric (ε = 3.2, tanδ = 0.04) on a liquid crystalline polymer laminate substrate that has a high 8 dBi gain at 24.5 GHz with a >33 dB S 11 [92]. Several horn-type antennas have also been demonstrated with the best performance going to a hybrid printing and plating process [114,115].…”
Section: Printed Antennasmentioning
confidence: 99%
“…These authors also showed a 14.6 dB return loss at 25.8 GHz. The first demonstration of a Yagi-Uda antenna was done a year earlier using IJP Ag (1.1 × 10 7 S/m) and SU-8 dielectric (ε = 3.2, tanδ = 0.04) on a liquid crystalline polymer laminate substrate that has a high 8 dBi gain at 24.5 GHz with a >33 dB S 11 [92]. Several horn-type antennas have also been demonstrated with the best performance going to a hybrid printing and plating process [114,115].…”
Section: Printed Antennasmentioning
confidence: 99%
“…New generation printers offer precise printing using picolitre volume cartridges. Printing quality is controlled by the jetting waveform, the jetting voltage of the nozzles, the jetting frequency, the cartridge temperature, the platen temperature (where the substrate is placed), and the resolution of the pattern [ 91 , 92 ]. After the printing of the antenna design, sintering is necessary for removing the solvent and capping agent and attaining electrical conductivity [ 93 ].…”
Section: Fabrication Techniques For Flexible Antennasmentioning
confidence: 99%
“…For example, a flexible inkjet-printed broadband UHF Radio Frequency Identification (RFID) on liquid crystal polymer (LCP) substrate is developed for sensing applications in [19]. A multilayer millimeter-wave yagi-uda antenna and proximity-fed patch arrays on flexible substrates using purely additive inkjet printing technology is proposed in [20], [21]. A compact inkjet-printed ultrawideband antenna on a Kapton polyimide substrate is used for flexible and wearable electronics in [22].…”
Section: Introductionmentioning
confidence: 99%